Analisis Kompetensi, Kecerdasan Emosional (EQ) Dan Kecerdasan Spiritual (SQ) Terhadap Kinerja Karyawan Lembaga Neptune Kediri - Eka Fitria Sari (Universitas Islam Kadiri, 2020)
Neptune is a one year educational hospitality training program institution which runs in the hospitality and work training sectors. As an hospitality and work training institution, all employees are required to be able to produce competent graduates who are ready for work. Moreover, nowadays, there are many new educational hospitality institutions in Indonesia, especially in East Java. If one institution is not be able to compete with its competitors, it will hardly struggle to produce competent graduates. As for the purpose of this research are : (1) To acknowledge if competence, emotional intelligence, and spiritual intelligence influences the performance of NEPTUNE Kediri's employees. (2) To acknowledge if competence influences the performance of NEPTUNE Kediri's employees. (3)To acknowledge if emotional intelligence influences the performance of NEPTUNE Kediri's employees. (4) To acknowledge if spiritual intelligence influences the performance of NEPTUNE Kediri's employees This research uses quantitative research. Population and sample of this research are all NEPTUNE's employees which is 33 in total. The technique uses in the sample taking is random sampling technique. The collected data are based on descriptively analyzed premier data and uses multiple linear regression analysis Based on the result of the analysis, can be concluded that : (1) Simultaneously (together with) competence , emotional intelligence, and spiritual intelligence have significant influences on the performance of NEPTUNE Kediri's employees . (2) Competence influences the performance of NEPTUNE Kediri's employees. (3) Emotional intelligence influences the performance of NEPTUNE Kediri's employees. (4) Spiritual intelligence influences the performance of NEPTUNE Kediri's employees From the results, then the researcher suggests that : (1) Neptune Kediri has to continue to observe how the employees perform and act, give service, impacts and effects, managerial ability, the power of thoughts or skill ability, personal effectiveness, several spiritual intelligence's points such as honesty, equity, self-awareness, focus on contribution, non dogmatic spiritual, openness is also has to be noticed to create good performance from the employees and to decline employees turnover. (2) The researcher is expected to expand this research because of the influences of the variables outside of the variable in this research.